The secret life of codes ; It's maths with the laughs added in! - Poskitt, Kjartan; Reeve, Philip (London : Scholastic, 2007)
Did you ever want to send a message that only your friend can read? Or did you want to try and uncover a secret communication from someone else? If so, then here's everything you need to know about creating and cracking codes--from the simplest substitution messages to the secrets of the well-known World War II coding contraption, the amazing Enigma Machine! The book includes information about: Substitution codes Scrambling codes Codes containing unrecognizable symbols Other message systems such as Morse code and flags And how to make your own Enigma machine! You'll be thrilled as this amusing book takes you on a codebreaking adventure, learning ways to decode both simple and difficult puzzles, as well as provides you with a history on the cryptology. Filled with tips and enjoyable illustrations by Ian Baker, Codes will have you sending secret messages in no time.
Keywords: Murderous Maths -- Nonfiction; Codes